2012
DOI: 10.1103/physrevb.86.104307
|View full text |Cite
|
Sign up to set email alerts
|

Length-dependent thermal conductivity of single extended polymer chains

Abstract: The low thermal conductivity of polymers will be one of the major roadblocks for the polymerbased microelectronics and macroelectronics due to the limited heat spreading capability. Despite that the thermal conductivity of bulk polymers is usually low, a single extended polymer chain could have very high thermal conductivity. In this paper, we present atomistic simulation studies on the phonon transport in single extended polymer chains of various polymers as a function of polymer chain length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
154
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(165 citation statements)
references
References 30 publications
(30 reference statements)
6
154
0
5
Order By: Relevance
“…In this pioneering work, it was found numerically that the thermal conductivity κ diverges with the system size N as κ ∝ N α with 0 < α < 1 which breaks the Fourier's heat conduction law [1]. Numerical simulations also confirm this anomalous heat conduction in diatomic Toda lattice [2], carbon nanotubes [3] and single polymer chains [4], to name a few. On the other hand, the 1D nonlinear lattices with external on-site potential such as Frenkel-Kontorova (FK) and φ 4 lattices show normal heat conduction [5][6][7].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In this pioneering work, it was found numerically that the thermal conductivity κ diverges with the system size N as κ ∝ N α with 0 < α < 1 which breaks the Fourier's heat conduction law [1]. Numerical simulations also confirm this anomalous heat conduction in diatomic Toda lattice [2], carbon nanotubes [3] and single polymer chains [4], to name a few. On the other hand, the 1D nonlinear lattices with external on-site potential such as Frenkel-Kontorova (FK) and φ 4 lattices show normal heat conduction [5][6][7].…”
Section: Introductionmentioning
confidence: 81%
“…Depends on the existence of onsite potential, the total momentum can be conserved or nonconserved. For φ 4 and combined (FK+φ 4 ) lattices, the total momentum is not conserved while the stretch diffusion is not normal. For FK lattice, the total momentum is not conserved and the stretch diffusion is normal.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the recent availability of low-dimensional materials, it remains to verify whether thermal conductivity is still size/geometry independent. For one-dimensional (1D) lattice models [1][2][3][4][5] and quasi-1D nanostructures and polymers [6][7][8] , a length dependence of k asBL b (L is sample length) has been predicted theoretically and then experimentally verified for nanotubes 9 . The same question remains open for two-dimensional (2D) systems.…”
mentioning
confidence: 99%
“…The class of materials that most closely resemble the 1D chains that have been studied previously [28][29][30][31][32] are polymers, specifically individual polymer molecules. Carbon nanotubes were once thought to also possibly exhibit divergence, but calculations performed by Mingo and Broido 29,33 as well as other molecular dynamics (MD) studies [34][35][36][37] confirmed that the thermal conductivity is large but still finite (non-divergent).…”
Section: Divergent Thermal Conductivity In Polymer Chainsmentioning
confidence: 99%